Proses Penetrasi Sosial Antar Pemain Pada Game Mobile Legends - Permassanty, Tanty Dewi; Irawan, Cornelius Hans (LONTAR: Jurnal Ilmu Komunikasi, 2018)
This study discusses the stage of development of social penetration relationship in Mobile Legends game which is seen through three factors of relationship development. The stage of interpersonal relationship development is the stage where two individuals who have not known each other to have an intimate relationship. Mobile Legends is a mobile game that is played in groups and requires interaction to work together. This interaction can be used to build interpersonal relationships. The theory used in this research is Social Penetration Theory. Social Penetration Theory is used to explain how the development of interpersonal relationships between Mobile Legends players. This research uses qualitative approach with constructivist paradigm. This research method is depth interview, observation, and literature study. The study looks at the stage of relationship development through three factors that influence the escalation of relationships, namely the attitude of trust, supportive attitude, and open attitude between players Mobile Legends. Open attitudes, supportive attitudes, and trust among Mobile Legends players have reached the affective exchange stage, that is, they are already open about personal information, romance, and family. Keywords: Developmental Stage of Interpersonal Relationship, Social Penetration Theory, Mobile Legends.